Recent advances in layer-by-layer assembled conducting polymer based composites for supercapacitors - Kulandaivalu, Shalini; Sulaiman, Yusran (MDPI, 2019)
Development of well-designed electrodes is the key to achieve high performance supercapacitors. Therefore, as one of the effective methods, a layer-by-layer (LBL) approach is often fruitfully employed for the fabrication of electrode material. Benefiting from a tunable parameter of the LBL approach, this approach has paved a way to design a highly ordered nanostructured electrode material with excellent performance. Conducting polymers (CPs) are the frontrunners in supercapacitors and notably, the LBL assembly of CPs is attracting extensive attention. Therefore, this critical review covers a comprehensive discussion on the research progress of CP-based composites with special importance on the LBL approach predominately for supercapacitors. Following a brief discussion on supercapacitors and CPs, the most up-to-date techniques used in LBL are highlighted.